Rare Pathology of Sinonasal Tract; Eosinophilic Angiocentric Fibrosis - Bahar Kayahan; Cavid Cabbarzade; Serdar Özer; Rıza Önder Günaydın; Ömer Taşkın Yücel (Turkish Archives of Otorhinolaryngology, 2014)

(untitled)
rare, benign and slowly progressive fibroinflammatory disorder, which mainly involves the upper respiratory tract. EAF was first described by Holmes and Panje in 1983. EAF is typically seen in young to middle-aged females and it has a slowly progressive nature. As well as the sinonasal region the nasal septum is mainly the most common localization of EAF, involvement of the larynx and orbita was also described in literature. Symptoms vary with the involved area but nasal obstruction, epistaxis and epiphora are the most common complaints. The etiology of EAF is not clear and it is diagnosed by specific histopathological features. Histologically, the lesion is characterized by a perivascular, eosinophil-rich inflammatory infiltrate and progressive fibrosis which appears as a whirling “onion-skin” pattern. In this paper; a case of sinonasal EAF is reported with the clinical course, radiological and histological features, etiology and treatment of these lesions based on updated literature.